Long noncoding RNA MACC1‐AS1 promotes the stemness of nonsmall cell lung cancer cells through promoting UPF1‐mediated destabilization of LATS1/2. Issue 9 (13th May 2020) - Wang, Xiaojun; Yu, Xinnian; Wei, Wei; Liu, Yuanhua
Abstract: The roles of long noncoding RNA (lncRNA) MACC1‐AS1 have been revealed in various tumors. This work aims to explore the roles of lncRNA MACC1‐AS1 in the stemness of nonsmall cell lung cancer (NSCLC) cells and the underlying mechanism. We showed that overexpression of MACC1‐AS1 enhanced the stemness of NSCLC cells, which is evident as the increased expression of cancer stem cell transcription factors, ALDH1 activity, and sphere‐formation capacity, while knockdown of MACC1‐AS1 decreased it. RNA‐sequencing analysis revealed that the Hippo pathway was mostly enriched in NSCLC cell with MACC1‐AS1 overexpression. Further mRNA and western blot analysis showed that ectopic expression of MACC1‐AS1 regulated the expression LATS1/2, the critical regulator of Hippo pathway. Additionally, it was found that MACC1‐AS1 interacted with up‐frameshift 1 (UPF1) to modulate mRNA decay of LATS1/2. Overexpression of LAST1/2 attenuated the promoting effects of MACC1‐AS1 overexpression on the stemness of NSCLC cells. Therefore, our results demonstrate the effects of the novel MACC1‐AS1/UPF1/LATS1/2 axis in NSCLC cell stemness.